Applying state space grids methods to characterize counsellor-client interactions in a physical activity behavioural intervention for adults with disabilities. (March 2023) - Hoekstra, Femke; Martin Ginis, Kathleen A.; Collins, Delaney; Dinwoodie, Miranda; Ma, Jasmin K.; Gaudet, Sonja; Rakiecki, Diane; Gainforth, Heather L.; ,
Abstract: Background: Physical activity (PA) counselling research has mainly focused on identifying which behaviour change techniques (BCTs) are delivered by a counsellor. Less is known about how BCTs are received by clients. State Space Grids (SSGs) is a dynamic system method that can be used to study counsellor-client interactions by examining frequencies, durations and sequences of BCT delivery and receipt. In this methods paper, we show how SSG methods can be pragmatically used to characterize counsellor-client interactions during a PA behavioural support intervention for adults with disabilities. Methods: Methods were demonstrated through a secondary analysis of data from adults with spinal cord injury (age: 45.79 ± 13.63; females: n = 5; males: n = 9) who received PA counselling. Transcripts of 30 audio-recorded counselling sessions (total duration: ∼8.3 h) were double-coded for BCT delivery and receipt statements using a reliable coding method (>84% agreement) and analyzed in two different ways using SSGs methods. Results: Applying the SSG analyses to our data demonstrated that frequencies, durations, and sequences of BCT delivery and receipt varied largely within and between dyads. Across all sessions, the counsellor and client spent on average 32–34% of their time on talking about BCTs related to goals and planning, ∼29% of their time talking about other BCTs (e.g., self-belief, support strategies), and the remaining 27–29% of their time talking about other topics (not BCT-specific). Conclusion: This paper showed how dynamic system methods can be pragmatically used to characterize counsellor-client interactions and illustrate the variability of how BCTs are delivered by a counsellor and received by clients in a PA behavioural support intervention. We demonstrated that SSGs methods can facilitate the examination of frequencies, durations and sequences of BCT delivery and receipt can help advance our understanding of PA behavioural support for adults with and without disabilities. Highlights: First using State Space Grids in exercise counselling in clients with disabilities. Demonstration of how behaviour change techniques are delivered and received. Show how State Space Grids may advance science and practice of exercise counselling.